2018
DOI: 10.1002/jcp.27252
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin attenuates glucocorticoid‐induced osteoporosis by regulating ERK/Lrp‐5/GSK‐3β signaling pathway in vivo and in vitro

Abstract: Glucocorticoid-induced osteoporosis (GIO) is a secondary osteoporosis with extensive use of glucocorticoids (GCs). GCs can increase bone fragility and fracture via inhibiting osteoblastic proliferation and differentiation. Luteolin (LUT), a kind of plant flavonoid, has been reported to exhibit the antioxidant activity, but the effects of LUT on GIO still remain unclear. This study aimed to investigate the effects of LUT on GIO both in vivo and in vitro and elaborate the potential molecular mechanisms. LUT incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…In addition, Jing et al. demonstrated decreased apoptosis and increased osteoblast differentiation via ERK/Lrp‐5/GSK‐3β pathway and elevated osteogenic markers, runt related x‐2, ALP, and osteoprotegerin/RANKL ratio after administration of 25, 50, and 100 mg/kg luteolin in rats with osteoporosis . Reduced MMP‐9 and MMP‐13 levels which indicate decreased collagen degradation, were also found in osteoblast cells subjected to luteolin .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Jing et al. demonstrated decreased apoptosis and increased osteoblast differentiation via ERK/Lrp‐5/GSK‐3β pathway and elevated osteogenic markers, runt related x‐2, ALP, and osteoprotegerin/RANKL ratio after administration of 25, 50, and 100 mg/kg luteolin in rats with osteoporosis . Reduced MMP‐9 and MMP‐13 levels which indicate decreased collagen degradation, were also found in osteoblast cells subjected to luteolin .…”
Section: Discussionmentioning
confidence: 97%
“…Luteolin is a plant‐derived compound with a proven anti‐osteoclastic and anti‐inflammatory activity . ‒ Therefore, based on the evidence present in the literature, present study hypothesized that “Luteolin, would prevent periodontal disease by decreasing inflammation and bone loss and increasing osteoblastic activity.” Therefore, present study aimed to evaluate possible effects of two different doses of luteolin on experimentally induced periodontitis model in rats. To achieve this purpose, morphometrical evaluation of mandibles, inflammatory cell counts, osteoblast and TRAP‐positive osteoclast cell counts, and immunohistochemical determination of inducible nitric oxide synthase (iNOS), bone morphogenetic protein (BMP)‐2, MMP‐8, tissue inhibitor of MMP (TIMP)‐1, RANKL, and osteoprotegerin (OPG) levels were performed.…”
Section: Introductionmentioning
confidence: 95%
“…In vitro studies have demonstrated that luteolin upregulates the expression of osteoblastic differentiation markers, including TGF-β1, BMP7, Runx-2, ALP, Osc, Osx, and collagen type I [34,88,89]. It also has anti-oxidative and anti-apoptotic effects on osteoblasts, in part via the regulation of the ERK/Lrp-5/GSK-3β signaling pathway [90][91][92]. Furthermore, luteolin diminishes osteoclastic differentiation and function in vitro and in vivo, increasing the bone mineral density and content of trabecular and cortical bones in ovariectomized rats [93,94].…”
Section: Luteolinmentioning
confidence: 99%
“…Yet, other authors using the same cellular type but much lower concentrations of this flavonoid have found that it prevented the osteoblastogenesis inhibition induced by glucocorticoids. Indeed, they showed that luteolin prevented bone mass loss, by downregulating apoptotic genes, increasing OPG / RANKL gene expression ratio, and activating the beta-catenin pathway in an animal model of osteoporosis induced by glucocorticoids[115]. Therefore, these results suggest that this compound has an osteoprotective role in bone marrow.…”
Section: Effects Of Unsaponifiable Fraction Of Olive Oil In Mscsmentioning
confidence: 99%